Gait analysis in children with cerebral palsy: are plantar pressure insoles a reliable tool? - Raposo, Maria Raquel (2022)
Cerebral palsy (CP) is a common cause of motor disability, and pedobarography is a useful, non-invasive, portable, and accessible tool; it is easy to use in a clinical setting; and can provide plenty of information about a foot–soil interaction and gait deviations. The reliability of this method in children with CP is lacking. The aim of this study is to investigate test-retest reliability and minimal detectable change (MDC) of plantar pressure insole variables in children with CP. Eight children performed two trials 8 ± 2.5 days apart, using foot insoles to collect plantar pressure data. Whole and segmented foot measurements were analyzed using intraclass correlation coefficients (ICC). The variability of the data was measured by calculating the standard error of measurement (SEM) and the MDC/ICC values demonstrated high test-retest reliability for most variables, ranging from good to excellent (ICC ≥ 0.60). The SEM and the MDC values were considered low for the different variables. The variability observed between sessions may be attributed to the heterogeneous sub-diagnosis of CP.